Invalidação de contratos administrativos e responsabilidade extracontratual da administração - Motta Neto, Berilo Pereira da (2023)
The present dissertation starts from a bibliographical analysis and has as motto to present sufficient elements to the composition factual support disposed in art. 149 of Federal Law No. 14.133/2021. It is intended, therefore, to establish parameters that give rise to the patrimonial responsibility of the Administration when resulting from the invalidation of public contracts signed with private individuals. The theme is justified, therefore, in terms of outlining the theoretical bases on how the State's responsibility is based on these hypotheses. To this end, develop an operational concept of administrative contract in the strict sense. Under a normative perspective, we proceeded to an analysis of important aspects of its invalidation. Next, we frame the hypotheses visited in the non-contractual liability of the State for the performance of the Administration, which is why the liability in question is objective in nature. Considering the numerous variables that could be aligned with the problem, starting from one already developed by the Brazilian doctrine of problem situations, we point out changes in the Brazilian legal system method that claim a distinction between competence (non-contractual liability) and obligations to reimburse (prohibition of unjust enrichment). In the hypotheses under examination, therefore, the responsibility of the State will only be involved when there is a positive action by the Administration, consisting of the enunciation of an invalid administrative contract, due to which the individual is included an indemnifiable damage, without this having concurred with guilt to the consummation of the targeted vice.